(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
Basing on detailed analysis of floristic and coenotic diversity and present-day state of Ukraine steppe zone natural and seminatural vegetation, graphic model of Ukraine steppe zone ecological network developed with emphasing its structural components of the international, national and regional levels.